Design and characterization of clindamycin-loaded nanofiber patches composed of polyvinyl alcohol and tamarind seed gum and fabricated by electrohydrodynamic atomization - Tanikan Sangnim; Sontaya Limmatvapirat; Jurairat Nunthanid; Pornsak Sriamornsak; Wancheng Sittikijyothin; Sumalee Wannachaiyasit; Kampanart Huanbutta (Elsevier, 2018)
In this study, we developed a polymeric nanofiber patch (PNP) for topical disease treatment using electrohydrodynamic atomization (EHDA). The nanofibers were prepared using various concentrations of polyvinyl alcohol (PVA) and tamarind seed gum and loaded with clindamycin HCl as a model drug. The precursor polymer solutions were sprayed using the EHDA technique; the EHDA processing parameters were optimized to obtain blank and drug-loaded PNPs. The skin adherence, translucence, and ventilation properties of the prepared PNPs indicated that they are appropriate for topical application. The conductivity of the polymer solution increased with increasing PVA and clindamycin concentrations, and increasing the PVA concentration enhanced the solution viscosity. Based on scanning electron microscopy analysis, the PVA concentration had a pronounced effect on the morphology of the sprayed product. Nanofibers were fabricated successfully when the solution PVA concentration was 10%, 13%, or 15% (w/v). The applied voltage significantly affected the diameters of the prepared nanofibers, and the minimum nanofiber diameter was 163.86 nm. Differential scanning calorimetry and X-ray diffraction analyses indicated that the model drug was dispersed in PVA in an amorphous form. The PNP prepared with a PVA:gum ratio of 9:1 absorbed water better than the PVA-only PNP and the PNP with a PVA:gum ratio of 9.5:0.5. Moreover, the PNPs loaded with clindamycin at concentrations of 1%-3% prohibited the growth of Staphylococcus aureus more effectively than clindamycin gel, a commercially available product. Keywords: Electrohydrodynamic atomization (EHDA), Polymeric nanofiber, Clindamycin, Wound dressing